Keuntungan Usahatani Kunyit (Curcuma domestica Val) Di Desa Maniapun Pengaron Kabupaten Banjar - Fenny Refiana; Triatmoko, Eddy; Fitriadi, Subhan (Fakultas Pertanian UVAYA Banjarmasin, 2023)
The purpose of this research is to know the revenue,the Total cost ,income and Profit. This research was conducted in Oktober– Desember 2023 at village Maniapun , Banjar regency. The sensus sampling methode used was by observing 9 farmers in village Maniapun who planted Turmeric plant.The Average land area 0,12/farmer,and Average result of the revenue is Rp. 3.013.888,89,/farmer, or Rp.25.115.740,75/Ha. The average Total cost is Rp. 1.216.035,29/farmer, and Average income profit Rp. 1.800.297,15/farmer, and From this result of development of farming Turmeric flant.We believe that it has good prospect and revenue, of the average profit income ,tecnicall,economically and increase in land area